The relationship between second-to-fourth digit (2D:4D) ratios and problematic and pathological Internet use among Turkish university students - Canan, Fatih (J Behav Addict, 2017)
BACKGROUND AND AIMS: The ratio of the second and fourth fingers (2D:4D ratio) is a sexually dimorphic trait, with men tending to have lower values than women. This ratio has been related to prenatal testosterone concentrations and addictive behaviors including problematic video-gaming. We aimed to investigate the possible association between 2D:4D ratios and Internet addiction and whether such a relationship would be independent of impulsivity. METHODS: A total of 652 university students (369 women, 283 men), aged 17–27 years, were enrolled in the study. Problematic and pathological Internet use (PPIU) was assessed using the Internet Addiction Test (IAT). The participants also completed the Barratt Impulsiveness Scale (version 11; BIS-11) and had their 2D:4D ratios measured. RESULTS: 2D:4D ratios were not significantly different in women with PPIU and in those with adaptive Internet use (AIU). Men with PPIU exhibited lower 2D:4D ratios on both hands when compared with those with AIU. Correlation analysis revealed that 2D:4D ratios on both hands were negatively correlated with IAT scores among men, but not among women. The multiple linear regression analysis revealed that age, duration of weekly Internet use, impulsiveness, and 2D:4D ratios on the right hand were independently associated with IAT scores among men, and impulsivity did not mediate the relationship between 2D:4D ratios and PPIU. CONCLUSIONS: For men, 2D:4D ratios on the right hand were inversely correlated with Internet addiction severity even after controlling for individual differences in impulsivity. These findings suggest that high prenatal testosterone levels may contribute to the occurrence of PPIU among men.